Stalkerzy vs Nocni Łowcy. Wizje męskości w uniwersach fantastycznych dla młodych mężczyzn i kobiet w Polsce - Gołuński, Mirosław (Śląskie Studia Polonistyczne, 2020)
The presented analysis juxtaposes a half-peripheral, essentially dystopian masculinity depicted in a Polish fantasy universe (including over 30 volumes by Polish and Russian authors of both genders) and a projected (utopian?) masculinity at the heart of another universe, most of all addressed to girls. Visions of masculinity presented in both the universes are the bases of comparative analysis conducted in the article. The differences between the considered warriors are made conspicuous within a few spheres of their relations and actions, from their purity and body care, to their attitudes to women and erotic relationships they engage in. What concludes the article is the analysis of the protagonists’ and narrators reactions to non-heteronormative behaviours (trace amounts of which appear in the world of the Factory Zone [Polish: Fabryczna Zona] novels, yet feature opulently and overtly in Shadowhunters).